The Migration Pattern of Florida Seasonal Farmworkers - Zhengfei Guan; Berdikul Qushim; Feng Wu; Alicia J. Whidden (EDIS, 2018)
This article investigates the migration pattern of seasonal farmworkers in the Florida strawberry industry based on a worker survey conducted in 2016. In the survey, we asked workers where they were working and what crops they were working on before this job. We also asked where they would migrate and what crops they would be working on after this job.  We found most workers were from Florida, Michigan, North Carolina, California in that order, and similar percentages of workers would migrate to these states after the job. Blueberries, tomatoes, and apples were the top three crops they were working on before and after the job.